In Vivo 18F‐Florzolotau Tau Positron Emission Tomography Imaging in Parkinson's Disease Dementia - Tang, Yilin; Li, Ling; Hu, Tianyu; Jiao, Fangyang; Han, Linlin; Li, Shiyu; Xu, Zhiheng; Fan, Yun; Sun, Yimin; Liu, Fengtao; Yen, Tzu‐Chen; Zuo, Chuantao; et al. (Movement disorders, 2023)
Background Tau pathology is observed during autopsy in many patients with Parkinson's disease dementia (PDD). Positron emission tomography (PET) imaging using the tracer 18F‐florzolotau has the potential to capture tau accumulation in the living brain. Objective The aim was to describe the results of 18F‐florzolotau PET/CT (computed tomography) imaging in patients with PDD. Methods Ten patients with PDD, 9 with Parkinson's disease with normal cognition (PD‐NC), and 9 age‐matched healthy controls (HCs) were enrolled. Clinical assessments and 18F‐florzolotau PET/CT imaging were performed. Results 18F‐Florzolotau uptake was significantly higher in the cortical regions of patients with PDD compared with both PD‐NC and HCs, especially in the temporal lobe. Notably, 18F‐florzolotau uptake in the occipital lobe of patients with PDD showed a significant correlation with cognitive impairment as reflected by Mini‐Mental State Examination (MMSE) scores. Conclusions 18F‐Florzolotau PET imaging can effectively capture the occurrence of tau pathology in patients with PDD, which was also linked to MMSE scores. © 2022 International Parkinson and Movement Disorder Society.